Use of scales and bones of white cachama (Piaractus brachypomus) and tilapia (Oreochromis spp.) as soil corrective (Revista Sistemas de Producción Agroecológicos, 2017)
The fish scale contains elements such as calcium, carbon and phosphorus, that can be used for agricultural productive purposes of importance to the region of the Colombian Orinoquia, enabling the replacement or reduction of agricultural chemicals that are currently used to fertilize the soil, therefore this work was done with the aim of finding possible alternative uses of the scales and bones of white cachama (Piaractus brachypomus) and red tilapia (Oreochromis spp.) that are produced as waste in restaurants, homes and fish farms, and some of them pour them into the surrounding natural environment, generating ecological impacts not yet evaluated. The extraction of the mineral and organic components present in the scale and bones was carried out, to later apply it on the floor of plots of one m2, established in the field and with previous chemical analysis of it to know its composition; in addition, a commercial product (dolomite lime) was used to compare the efficiency of the two amendments. Differences were found (p
Keywords: amendment; compost; fertilizer; acid soil; agriculture